The IAG-Switch and Further Transcriptomic Insights Into Sexual Differentiation of a Protandric Shrimp - Levy, Tom; Tamone, Sherry L.; Manor, Rivka; Aflalo, Eliahu D.; Sklarz, Menachem Y.; Chalifa-Caspi, Vered; Sagi, Amir (Frontiers in Marine Science, 2020)
The insulin-like androgenic gland hormone (IAG) secreted from the androgenic gland (AG) is a unique endocrine controller (the IAG-switch) of crustacean sexual differentiation. However, while previous studies of the IAG-switch focused mainly on sexual differentiation at early developmental stages of gonochoristic species, this mechanism is yet to be deciphered during naturally occurring sexual shifts in hermaphrodite species. The Northern spot shrimp, Pandalus platyceros, is a protandric hermaphrodite species, native to the North Pacific Ocean. We collected four stages of spot shrimp in Southeast Alaska including: juveniles, adult males, transitionals and adult females. The AG was dissected from each stage and characterized histologically. Additionally, the IAG mRNA was sequenced. The function of the IAG-switch during the life history of this protandric species was demonstrated through monitoring IAG gene expression. Transcript levels were highest at the juvenile stage, then decreased significantly in mature males and became negligible in the transitional and female stages. Moreover, manipulating the IAG-switch via IAG loss of function in males through RNAi, induced the expected masculine to feminine sexual transformation that naturally occurs in this species. This included reduction in IAG transcript levels in males, elevation of vitellogenin gene expression in hepatopancreas and transformation of the gonad from an ovotestis containing both ovarian and testicular tissue to a true ovary with vitellogenic oocytes. Furthermore, a transcriptomic library from tissues associated with the endocrine axis upstream and downstream the IAG-switch yielded 1,801, 1,707, 1,946 and 182 differentially expressed genes between males, transitionals and females in the AG, eyestalk, gonad and hepatopancreas, respectively. Among these genes, the transcriptional pattern of six of them (all of them in the AG), between males, transitionals and females, had similar or inverted transcriptional pattern to that of IAG in P. platyceros. Five of these putatively IAG-switch associated genes are downregulated and one is upregulated throughout the P. platyceros shift from maleness to femaleness. Homolog protein sequences for the above novel genes were found in 17 other decapod species suggesting that they might represent conserved factors associated with the IAG-switch and involved in universal crustacean sexual differentiation mechanisms.